PENGARUH BRAND LOVE DAN E-WOM TERHADAP CUSTOMER ENGAGEMENT PADA PRODUK SKINTIFIC DI TIKTOK SHOP (STUDI KASUS MAHASISWA FEB UNIVERSITAS MUHAMMADIYAH BENGKULU) - Della Wahyuni Puspita Sari; Reni Indriani (Yayasan Insani Mandiri Santani, 2025)
Skintific products are one of the brands that utilize TikTok Shop, successfully attracting consumers' attention with a more personal and interactive approach and building closer relationships with its users through Brand Love and e-WOM strategies. This study aims to analyze the effect of brand love and e-WOM (electronic word of mouth) on customer engagement on Skintific products on TikTok Shop. The respondents used were 140 FEB students from Bengkulu University through an online survey. Respondents were selected purposively, namely respondents aged 18-30 years and had experience with Scientific products, especially on TikTok Shop. The data obtained were then analyzed using a multiple linear regression model. The results of the study showed that brand love had a positive effect on customer engagement on Skintific products on TikTok Shop, with the results of the t_count test > t_table (3.199 > 2.266). Then, E-WOM had a positive effect on customer engagement on Skintific products on TikTok Shop, with the results of the t_count test > t_table (9.361 > 2.266). Furthermore, Brand love and e-WOM have a positive effect on customer engagement on Skintific products on TikTok Shop with the results of the F_count test 118.418 > F_count 19.488. Keywords: Customer Engagement, Brand Love, E-Wom, Tiktok Shop